Differential Ion Mobility–Mass Spectrometry for Detailed Analysis of the Proteome. Issue 2 (February 2019) - Winter, Daniel L.; Wilkins, Marc R.; Donald, William A.
Abstract : The field of proteomics is increasingly concerned with the diversity and functional relevance of protein modifications. Differential ion mobility spectrometry (DMS) is emerging as a tool to detect and quantify additional peptide and protein species that are difficult to analyse with conventional instrumental methods. In this review, recent advances in DMS are discussed, with a focus on the different types of DMS instruments now available to researchers in proteomics. Furthermore, the combination of DMS with mass spectrometry (MS) for increased proteome coverage and the targeted analysis of modification patterns on single proteins is highlighted. Frontier areas of research, such as the analysis of intact proteoforms, and future directions for the implementation of DMS in proteomics are also discussed. Highlights: DMS can be used to rapidly separate ions prior to MS analysis. Compared to drift tube-based IMS, ion separation by DMS is more orthogonal to MS. The implementation of DMS in MS workflows has improved the coverage and quantification of proteomes, including the large-scale analysis of PTMs. High-resolution DMS can separate isobaric peptides that are otherwise challenging to separate by use of conventional chromatography methods, including peptides that differ by the position of a single methyl group. DMS combined with other gas-phase separation methods in tandem ion mobility can provide an alternative to LC, for exceptionally high-throughput proteomic analyses.